Implementation of the Strategy for Memorizing Arabic Vocabulary with the Hanifida Method - Ahmad Rouyani Al Bahroni; Muhammad Arif Setia Budi (Dzihni: Jurnal Pendidikan Bahasa Arab, Linguistik dan Kajian Literatur Arab, 2023)
Arabic is one of the foreign languages developed in educational institutions in Indonesia, especially in Islamic boarding schools and educational institutions with Islamic characteristics, even in government schools that have language majors. Ahmed Fuad Effendi said, "Vocabulary is one of the elements of a language that foreign language learners must master so that they can gain proficiency in communicating with that language." The research questions of this research are: How is the application of strategies for memorizing Arabic vocabulary using the Hanifida method in the High School of the Qurâ€™an, La Raib Hanifida? What are the supporting factors and the inhibiting factors in the application of strategies for memorizing Arabic vocabulary using the Hanifida method in the High School of the Qur'an, La Rayeb Hanifida? The research method is qualitative research using the classroom approach. Its type is case study research. Data collection method by observation, interview, and documents. Data analysis method, including data reduction, data presentation and conclusions. And the method of correctness of data, including drums observation, promotion of willpower and triangulation. As for the results of this research, it can be summarized as follows: 1) The application and strategies of memorizing the Hanifida method in memorizing vocabulary in the high school, no doubt Hanifada, which is the use of the correlation system. That is, combining vocabulary and translating it in the form of a story, arranging the story from it in a sentence, applying the strategy of memorizing vocabulary in the Hanifida method, practically applying two of the five systems, including the story system and the replacement system. 2) The supporting factors and the inhibiting factors in memorizing vocabulary by Hanifeda's method in the high school. The first obstacle is the number of vocabularies that students must memorize, and the second is some key words that are difficult to imagine.Â